2021
DOI: 10.1007/s00330-020-07679-8
|View full text |Cite
|
Sign up to set email alerts
|

How does image quality affect radiologists’ perceived ability for image interpretation and lesion detection in digital mammography?

Abstract: Objectives To study how radiologists’ perceived ability to interpret digital mammography (DM) images is affected by decreases in image quality. Methods One view from 45 DM cases (including 30 cancers) was degraded to six levels each of two acquisition-related issues (lower spatial resolution and increased quantum noise) and three post-processing-related issues (lower and higher contrast and increased correlated noise) seen during clinical evaluation of DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…A higher J or IoU score brings better similarity between the two sets. The accuracy of the segmentation was measured based on its testing performance on different input image settings, based on Equation (11), utilizing TP, FP, TN, and FN.…”
Section: Mass Segmentation and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher J or IoU score brings better similarity between the two sets. The accuracy of the segmentation was measured based on its testing performance on different input image settings, based on Equation (11), utilizing TP, FP, TN, and FN.…”
Section: Mass Segmentation and Evaluationmentioning
confidence: 99%
“…Past studies concluded that mass detection decreased with increased density, due to the mass itself being similar to the surrounding dense tissue of the breast [8][9][10]. Additionally, image quality conditions also make it difficult to detect the lesion in dense breasts [11,12]. Specifying the edge of the mass from its surrounding dense tissue requires image processing that enhances the textural element of the image as one of the defining mass descriptors to assess a mammogram visually [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are in turn altered by parameters related to the image acquisition process, such as breast compression and thickness, which aims at minimizing scattered radiation and thus increasing contrast and SNR, positioning, the x-ray beam quality (determined by the anode/filter combination and voltage), and the radiation dose. 7,8 Furthermore, these parameters may affect differently in the detection of different findings suggesting breast cancer, which are mainly soft-tissue lesions and calcifications. 9,10 In the case of the former, the margins delimiting the lesion and its density are determinants of its malignancy, whereas in the case of calcifications, their number, morphology and distribution predominate.…”
mentioning
confidence: 99%
“…9,10 In the case of the former, the margins delimiting the lesion and its density are determinants of its malignancy, whereas in the case of calcifications, their number, morphology and distribution predominate. 8 Thus, factors, such as contrast, may affect more severely the detection of soft-tissue lesions, whereas spatial resolution or noise may be more decisive in detecting calcifications. 11,12 In addition, breast density (i.e., the percentage or absolute amount of fibroglandular tissue) is also known for being an essential factor affecting image quality.…”
mentioning
confidence: 99%